2014
DOI: 10.1111/ijfs.12596
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐related differences in the nutritional value of Japanese quail meat

Abstract: The objective of the study was to evaluate the impact of birds' sex on the carcass composition and meat (breast muscle) nutritional value in Japanese quails in a large-scale four-generation study. Standard poultry feed was used, based on maize, soya bean meal and wheat. Four generations of quails were housed up to the age of 17 weeks each. Then samples of breast muscle were collected after dissection and analysed for basic nutrient content and for fatty acids composition. Results were analysed by GLM procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…; P<0.05), with a higher (P<0.01) proportion of linoleic and linolenic acids. Sartowska et al (2014) found that oleic, linoleic and α-linolenic acids were significantly higher in female Japanese quail meat, while palmitic, stearic and arachidonic acids were significantly higher in meat from males, indicating that sex had a marked influence on the fatty acid profile. Females had higher (P<0.05) amount of total n-6 FA and a lower (P<0.05) TI compared to males.…”
Section: Total Lipid Cholesterol Contents and Fatty Acid Compositionmentioning
confidence: 91%
See 1 more Smart Citation
“…; P<0.05), with a higher (P<0.01) proportion of linoleic and linolenic acids. Sartowska et al (2014) found that oleic, linoleic and α-linolenic acids were significantly higher in female Japanese quail meat, while palmitic, stearic and arachidonic acids were significantly higher in meat from males, indicating that sex had a marked influence on the fatty acid profile. Females had higher (P<0.05) amount of total n-6 FA and a lower (P<0.05) TI compared to males.…”
Section: Total Lipid Cholesterol Contents and Fatty Acid Compositionmentioning
confidence: 91%
“…Effects of factors such as breed, age, sex and nutritional condition on fat deposition and FA profile of Japanese quail are not widely studied. In fact, very few studies on the FA composition and cholesterol content of Japanese quail meat have been published (Botsoglou et al, 2004;Genchev et al, 2008;Boni et al, 2010;Sartowska et al, 2014;Gecgel et al, 2015;Yalcin et al, 2017), and available results are not always directly comparable. In addition, far too little attention has been paid to the determination of meat quality traits of adult or spent quails at the end of their productive life (Santhi and Kalaikannan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Genchev et al (2008) detected higher lipid content in female carcasses with skin than those of male ones, while meat dry matter, protein, and ash contents were not significantly different between the 2 genders. Further, Sartowska et al (2014) reported no differences in the breast meat content of protein and ash between males and female. In contrast, Magubane et al (2013) detected similar fat content in the breast muscles of males and females.…”
Section: Discussionmentioning
confidence: 90%
“…Quail meat is of good quality because it contains 23% protein and a fat content of less than 3% ( Daikwo et al, 2013 ; Alagawany et al, 2014 ). The age of quail birds significantly affects live weight ( Boni et al, 2010 ), carcass ( Kumar et al, 2011 ; Sartowska et al, 2014 ), and the quality of the meat ( Genchev et al, 2008 ; Choi et al, 2012 ). The growing interest in producing Japanese quail in emerging nations results from the tremendous chance for diversity and early marketability that quail breeding provides.…”
Section: Introductionmentioning
confidence: 99%